2021
DOI: 10.3390/ijerph18179023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Passion and Achievement Goals in Optimal Functioning in Sports

Abstract: This study aimed to test the role of passion in the cognitive goals pursued in sport and the level of Optimal Functioning in Society (OFIS) derived from such sport engagement. A total of 184 competitive water polo and synchronized swimming athletes completed a questionnaire assessing their passion for their sport, achievement goals, and various scales assessing their level of OFIS (e.g., subjective well-being, relationship with their coach, sport performance, and intentions to continue in sport). It was hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…This agrees with results that corroborate previous studies revealing that HP supports wellbeing evidences such as self-esteem (St-Cyr et al, 2021;Peixoto et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This agrees with results that corroborate previous studies revealing that HP supports wellbeing evidences such as self-esteem (St-Cyr et al, 2021;Peixoto et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…As defined psychologically, passion refers to time and energy spent by an individual on what he admires or likes and believes is important for him (Vallerand et al, 2003;Vallerand, 2008;St-Cyr et al, 2021). Vallerand (2010) notes that the concept of passion has had several definitions.…”
Section: Review Of Literature: Passionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous research, our results suggest that HP promotes a balanced road throughout sport engagement, allowing one to fully develop as an individual within a team environment [3,15,16,18]. In general, HP allows athletes to adopt mastery goals leading them to fully embrace the team orientation and a collaborative approach [24,25].…”
Section: Discussionsupporting
confidence: 89%
“…Research on the role of passion in the use of achievement goals has shown that HP for a sport leads to more adaptive mastery goals (i.e., trying to master the activity), while OP has been found to be associated with mostly performance-approach (i.e., trying to do better than others) and performance-avoidance goals (i.e., trying to avoid doing worse than others) [14][15][16][17]. The relationship between OP and mastery goals is less clear since past research has shown positive [15,16,18] or non-significant [17,19] relationships between these variables.…”
Section: Introductionmentioning
confidence: 99%